Unique Pattern of Aortic Regurgitation Caused by Rupture Into the Left Ventricular Interleaflet Triangle of a Sinus Valsalva Aneurysm Involving the Left Coronary Cusp. (November 2017) - Mochizuki, Yasuhide; Iwahashi, Kazuhiko; Nakagiri, Keitaro; Shite, Junya
Abstract : Supplemental Digital Content is available in the text.